Defect‐tolerance analysis of fundamental quantum‐dot cellular automata devices. Issue 4 (7th April 2015) - Zhang, Yongqiang; Lv, Hongjun; Liu, Shuai; Xiang, Yunlong; Xie, Guangjun
Abstract : Quantum‐dot cellular automata (QCA) is a burgeoning technology at the nano‐scale range, with the potential for lower power consumption, smaller size and faster speed than conventional complementary metal–oxide semiconductor‐based technology. Because of its ultra‐density integration and its inherent physical properties, fault‐tolerance is an important property to consider in the research and manufacture of QCA. In this paper, one type of defect, in which displacement and misalignment occur coinstantaneously, is investigated in detail on rudimentary QCA devices (majority voter (MV), inverter, wire) with QCADesigner. Another MV with rotated cells is also proposed, and it is more robust than the original one. Simulation results present the defect‐tolerance of these devices, that is, the maximum precise region the defective cell can be moved moreover, with correct logical function. These conclusions have a meaningful guiding significance for QCA physical implementation and fault‐tolerance research.